2022
DOI: 10.3390/ijms232314895
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide (VIP) Protects Nile Tilapia (Oreochromis niloticus) against Streptococcus agalatiae Infection

Abstract: Vasoactive intestinal peptide (VIP), a member of secretin/glucagon family, is involved in a variety of biological activities such as gut motility, immune responses, and carcinogenesis. In this study, the VIP precursor gene (On-VIP) and its receptor gene VIPR1 (On-VIPR1) were identified from Nile tilapia (Oreochromis niloticus), and the functions of On-VIP in the immunomodulation of Nile tilapia against bacterial infection were investigated and characterized. On-VIP and On-VIPR1 contain a 450 bp and a 1326 bp o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Myeloid differentiation factor 88 (MyD88) is a main component of MyD88‐dependent pathway, which can lead to the production of inflammatory cytokines (Gao et al, 2022). GBS infection can cause the expression of myd88 in tilapia (Zhang, Li, et al, 2022). Interestingly, medicinal plants play important roles in downregulating the expression of myd88 .…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid differentiation factor 88 (MyD88) is a main component of MyD88‐dependent pathway, which can lead to the production of inflammatory cytokines (Gao et al, 2022). GBS infection can cause the expression of myd88 in tilapia (Zhang, Li, et al, 2022). Interestingly, medicinal plants play important roles in downregulating the expression of myd88 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with VIP for 6 h increased the relative expression levels of anti-inflammatory cytokines such as IL-10 and TGF-β in different tissues. In addition, there was also a significant increase in the expression of pro-inflammatory cytokines such as IL-1β and TNF-α at 6 h of treatment in the head kidney [ 33 ]. Therefore, these studies suggest that in teleosts, VIP and ghrelin induce both pro- and anti-inflammatory responses, different from those observed in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in the species Paralichthys olivaceus , an increase and a decrease in VIP expression in the spleen and head kidney were observed when an in vivo challenge with Edwardsiella tarda was performed [ 32 ]. On the other hand, in research on the species Oreochromis niloticus , it was concluded that VIP would present several immunological functions, such as decreasing the expression of pro-inflammatory cytokines and increasing the expression of anti-inflammatory cytokines, reducing the expression of genes involved in inflammation signaling and protection against Streptococcus agalatiae infection [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the hematoxylin and eosin (H&E) staining and immunofluorescence (IF) assay, the procedures described in our previous work ( 25 , 33 ) were followed. Briefly, the whole brains of healthy fish were isolated and fixed in Dietrich’s fixative for 24 hours.…”
Section: Methodsmentioning
confidence: 99%